2012
DOI: 10.1111/j.1538-7836.2012.04880.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and the risk of venous thromboembolism: The Tromsø Study

Abstract: Summary. Background: Conflicting findings have been reported on the association between smoking and the risk of venous thromboembolism (VTE). Objectives: To conduct a prospective, population-based cohort study to investigate the association between cigarette smoking and the risk of incident VTE. Patients/Methods: Information on smoking habits was assessed by self-administered questionnaires in 24 576 subjects, aged 25-96 years, participating in the fourth Tromsø Study in 1994-1995. Incident cases of VTE were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
5
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 34 publications
3
60
5
4
Order By: Relevance
“…Any association between COPD and risk of VTE may be affected by confounders. Smoking is the leading cause of COPD [33] and is also associated with risk of VTE in some [34,35], but not all [36,37], cohort studies. In our study, the impact of COPD on the risk of VTE remained unchanged after adjustment for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Any association between COPD and risk of VTE may be affected by confounders. Smoking is the leading cause of COPD [33] and is also associated with risk of VTE in some [34,35], but not all [36,37], cohort studies. In our study, the impact of COPD on the risk of VTE remained unchanged after adjustment for smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Although literature shows a 2-to 4-fold increase in thrombotic risk of hormonal therapy, we found no association with VTE, mainly due to the low prevalence (1.83% in VTE and 5.07% in women with VTE) and thus, we did not detail the analysis (according to the dose, route of administration) [8]. Smoking may represent a weak risk factor for DVT, especially in studies considering VTE events as the only outcome [19]; we found smoking to be relatively frequent in VTE (32.9%), but not enough to be independently associated with thrombotic risk. Family history is an independent risk factor for VTE, reflecting a hereditary thrombophilia [20].…”
Section: Discussionmentioning
confidence: 70%
“…The Tromsø study identifi ed an increased risk of 1.5 of total VTE and 1.8 in provoked VTE in heavy smokers (>20 pack-years). 15 Heavy smokers showed a higher incidence of VTE compared to nonsmokers or moderate smokers when combined with the heterozygous Factor V Leiden mutation. 16 Smoking may have contributed to our patient's fi rst VTE (2008), but it could not have been a contributing factor with his second VTE because he quit smoking in 2008.…”
Section: Discussionmentioning
confidence: 93%